Pengaruh Pemberian Dosis Pakan terhadap Pertumbuhan Benih Ikan Nila di Keramba Jaring Apung di Kabupaten Pohuwato - Bulotio, Nur Fitriyanti; Hamzah, Harisa; Djamil, Cahniar; Ndara, Niken (The NIKe Journal, 2023)
Tilapia is one type of fish that has great potential to be cultivated intensively in floating net cages because tilapia has beneficial biological characteristics, namely fast growth, omnivorous, broad adaptability, high tolerance to various environmental conditions, and more resistant to disease attacks. The aim of this research was to determine the effect of feed dosage on the growth of tilapia fish (orechromis niloticus) and the best feed dosage for the growth of tilapia fry (oreochromis niloticus). The method used in this research is the single factor Completely Randomized Design (CRD) method, namely giving different feed doses with 4 treatments repeated 3 times, so that there are 12 rearing experimental units carried out for 63 days. Each experimental unit was filled with 250 tilapia fish seeds in cage containers. The results of the study showed that there was an effect of giving fish food doses on the growth of tilapia fish. From the results of the anova test, the results were significantly different, but treatments P2 and P3 showed the same results for fish length. The P4 treatment with a 20% feed dose had good growth in weight and length of fish for 9 weeks when compared to P3, P2 and P1. For fish weight in the P4 treatment, the 20% feed dose was 56.05 grams, while for fish length it was 20.5 cm. For P3, P2 and P1 the weight of the fish was 50.2 gr, 50.6 gr and 42.7 respectively. Meanwhile, the fish lengths for P3, P2 and P1 were 19.5 cm, 19 cm and 17.75 cm respectively.